2011
DOI: 10.1177/0748730410391619
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Human Circadian Phase via a Multi-Channel Ambulatory Monitoring System and a Multiple Regression Model

Abstract: Reliable detection of circadian phase in humans using noninvasive ambulatory measurements in real-life conditions is challenging and still an unsolved problem. The masking effects of everyday behavior and environmental input such as physical activity and light on the measured variables need to be considered critically. Here, we aimed at developing techniques for estimating circadian phase with the lowest subject burden possible, that is, without the need of constant routine (CR) laboratory conditions or withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 27 publications
2
35
1
Order By: Relevance
“…Ortiz-Tudela et al (2010) suggested an integrated variable, based on thermometry, actimetry and body position to reduce individual recording artefacts and showed that it is well correlated with rest-activity logs. Kolodyazhniy et al (2011) evaluated circadian phase estimation using standard least squares algorithmic regression techniques on skin temperatures, accelerometry and ambient light level in the blue spectral band and showed a statistically significant improvement of variance of prediction error over traditional single predictor methods.…”
Section: Monitoring Modalitiesmentioning
confidence: 99%
“…Ortiz-Tudela et al (2010) suggested an integrated variable, based on thermometry, actimetry and body position to reduce individual recording artefacts and showed that it is well correlated with rest-activity logs. Kolodyazhniy et al (2011) evaluated circadian phase estimation using standard least squares algorithmic regression techniques on skin temperatures, accelerometry and ambient light level in the blue spectral band and showed a statistically significant improvement of variance of prediction error over traditional single predictor methods.…”
Section: Monitoring Modalitiesmentioning
confidence: 99%
“…With regard to evening-type, morning-type people show a 2–4 h advance in circadian phase in variables like subjective alertness, sleep times, core body temperature (CBT) or distal skin temperature (DST) [16]–[20]. Given that DST is closely associated to the CBT rhythm (showing an advanced rhythm phase and inverse temporal curve with maximum values within the sleeping period) [21], DST has been proposed as a reliable circadian index under free-living conditions [22], [23]. Additionally, infraclavicular temperature and the difference between distal and proximal temperatures (distal-proximal gradient, DPG) have been related to the vigilance state.…”
Section: Introductionmentioning
confidence: 99%
“…Some commonly used signals are activity level, light exposure Kronauer et al, 1999;St. Hilaire et al, 2007b;Mott et al, 2011), and skin temperature (Kolodyazhniy et al, 2011(Kolodyazhniy et al, , 2012. The drawback with these methods is that they require the collection of data over extended periods of time, in some cases up to 1 week, to obtain accurate results.…”
mentioning
confidence: 99%